Correct citation and lectotype designation for the name Iberis carica (Brassicaceae) - Çitak, Burcu Yilmaz; Crespo, Manuel B. (Phytotaxa, 2019)
The name Iberis carica (Brassicaceae) applies to an endemic annual species growing in southwestern Turkey. A lectotype is selected among syntypes cited in the protologue. Furthermore, the correct authorship citation of that name at both subspecific and specific ranks is discussed.